Migrant Labor Remittances in South Asia - Maimbo, Samuel Munzele; Adams, Richard H. Jr.; Aggarwal, Reena; Passas, Nikos (Washington, DC: World Bank, 2012)
This paper provides a strategic overview of key issues relating to the remittance industry in the South Asia region. The paper builds on recent research on remittances that prominently features the South Asia region. Rather than duplicate that work, this study focuses only on the region's distinguishing characteristics, namely: a large migrant population of semiskilled and unskilled workers largely concentrated in the Persian Gulf countries, particularly Saudi Arabia and the United Arab Emirates, contributing to rising remittance flows; the presence of dedicated public institutions and government financial incentives aimed at facilitating and providing support for temporary migration and remittance inflows; the existence of large state bank branch networks with immense potential for a more effective and efficient remittance financial market; and the widespread use of trade-related informal remittance channels by both legal and illegal migrants.